THE ROLE OF CYP2E1 POLYMORPHISM IN THE ACTIVATION OF PROCARCINOGEN METABOLISM OF NASOPHARYNGEAL CARCINOMA - Farhat Farhat; Elvita Rahmi Daulay; Jessy Chrestella (TALENTA PUBLISHER, 2019)
Intoduction: Cytochrome P450 2E1 (CYP2E1) is the enzyme as a part of CYP 450 enzyme families. It acts in phase I metabolism which result in the formation of electrophilic molecule and elevation of reactive oxygen species (ROS). Review: The last is responsible in development of cancer by damaging the protein and DNA, leading to mutation and increase cell proliferation. Nitrosamine as the most carcinogen for nasopharyngeal carcinoma (NPC) is the substrate of this enzyme. This chemical is contained in the salted fish, tobacco smoke, beer, and preserved food such as meat product. Nitrosamine needs CYP2E1 to activate the pro-carcinogen in order to act is carcinogenic effect. Polymorphism of CYP2E1 is associated with higher transcriptional activity and enzyme activity. Conclussion: It means the ability of this enzyme to activate pro-carcinogen of nitrosamine will increase, leading to higher chance to develop cancer, including NPC.